THE PARADOX OF ARTIFICIAL INTELLIGENCE USAGE IN HIGHER EDUCATION: BETWEEN ENHANCING LEARNING EFFECTIVENESS AND THE DECLINE OF STUDENTS CRITICAL THINKING SKILLS - Rizal Mulya Arif; Rahma Nisa; Zaidi Seif Allah (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This study explores the impact of artificial intelligence (AI) utilization in learning among students from diverse backgrounds, involving two subject groups: 15 Indonesian students analyzed through their academic assignments and 70 international students from Indonesia, China, Malaysia, and Tunisia surveyed via questionnaire. Task analysis employed an AI checker to measure AI’s contribution, while the questionnaire assessed students’ perceptions of AI’s impact. Results indicate that students in both high AI use (>60%) and low AI use (<60%) groups consistently achieved high academic grades (A and A-). The average scores for learning effectiveness across all countries were in the high category (Indonesia 3.03, China 3.05, Malaysia 3.16, Tunisia 3.01). However, there were signs of declining critical thinking skills, with scores ranging from 2.3 to 2.68. These findings underscore the need for balanced policies in AI adoption to enhance both learning quality and students’ critical thinking competencies, ensuring that technological advancement supports, rather than diminishes, essential academic skills.Keywords: Artificial intelligence, learning effectiveness, critical thinking, cognitive offloading, higher education